ANALISIS WACANA KRITIS DALAM PEMBERITAAN DARING TENTANG ISU KORUPSI DI PERTAMINA: PERSPEKTIF VAN DIJK - Ryega Daud Ibrahim; Kundharu Saddhono; Budhi Setiawan (Universitas Batanghari, 2025)
Bold news reporting is not just about conveying facts, but can also influence the public's and society's perspective on corruption issues involving state enterprises. The study aims to classify and explain the contents of bold news reporting on corruption issues at PT Pertamina based on Van Dijk's perspective. This study uses a qualitative method with a critical analysis discourse approach (AWK). The research data are in the form of three news texts with different titles taken from the dare mass media portal by Kompas.com, Okezonenews, and Tirto.id. Data validation The study conducted triangulation of methods, sources, and theories to test the validity of the data. Data collection techniques used data reduction, data presentation, and data verification. The findings showed that the mass media were not completely neutral in conveying news. This refers to the macro-structure aspect that the news texts published by Kompas.com, Okezonenews, and Tirto.id. have different delivery styles while the superstructure has continuity of information, then the microstructure of each news item displays ideological and power tools that shape opinions. Critical discourse analysis in Van Dijk's perception describes the social reality that communication of information on corruption issues at PT Pertamina has become an informational scheme that forms ideological and power practices